The effect of chemical and mineralogical composition of red mud on alkalinity parameters - Ljubica Vasiljević; Gordana Ostojić (Zaštita Materijala)
Red mud is highly alkaline colloidal suspension, which remains after processing bauxite into alumina by Bayer’s proceedings. Despite repeated washing red mud keep strong alkalinity, due to the presence of residual base and a number of alkaline minerals. This paper examines aspects of Bayer’s processes that affect the formation of alkalinity in the mud, and chemical reactions are considered significant for neutralization. Chemical and mineralogical content of red mud varies over a wide range. In the red mud appears a large number of minerals. Part of minerals that occur in the red mud originates from bauxite (insoluble minerals during leaching), and other minerals were synthesized due to the effect of process conditions on bauxite. These newly created minerals contribute significantly to the alkalinity of the red mud. Alkalinity of the red mud is most easily considered through the pH value. The pH of the solid phase of sludge is generally in the range from 10.5 to 12.5, and it is strongly buffered due to the presence of more alkaline minerals (hydroxides, carbonates, aluminates, and aluminosilicates). The presence of more buffering substances in the mud, causing a complex behavior of mud in the neutralization of acids. On neutralization curves are observed inflection points that are not typical of the pure substance. In addition to dissolving minerals holder alkaline anion, when considering the alkalinity should be considered alkaline anion exchange reactions occurring on the surface of metal oxides. Alkaline minerals are generally insoluble or poorly soluble in water, and dissolved in mineral acids. Therefore, the alkalinity of the red mud is very difficult to remove by washing with water. Treatment of mud with mineral acids, CO2, and gypsum causes a decrease of alkalinity. Aged sludge tailings also contributes to lowering the alkalinity. Finally, the alkalinity of the red mud is necessary to remove, as it is the undesirable property with a wide range of negative impacts. Knowledge of the neutralization mechanisms and dissolution, can contribute to the efficiency of the neutralization and finding new procedures, as well as different applications of neutralized red mud.